PENGARUH FOOD QUALITY DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO ROTI KHASANAH SARI DI KARAWANG - Rizka Dwi Syaharani; Riani Rahma Novelina; Salma Nurhasanah; Asep Maulana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Khasanah Bakery is one example of a bakery that has grown rapidly in Karawang. Khasanah Bakery competes with other bakeries by offering a variety of products and services. Competition in the culinary field is very high, ranging from roadside stalls to large, luxurious restaurants. This study aims to analyze the simultaneous and partial effects of food quality and brand image on purchasing decisions at Khasanah Sari Bakery, Unsika Branch, Karawang. Using an associative quantitative approach, this study involved 100 respondents who had purchased bread at the store as the population and sample through saturated sampling technique. Primary data was collected through a questionnaire using a Likert scale. Data analysis included validity and reliability tests, classical assumption tests (normality, multicollinearity, heteroscedasticity), multiple linear regression analysis, and F and t hypothesis tests. Based on the study, food quality and brand image are equally important and have a significant effect on purchasing decisions at the Khasanah Karawang Bakery. Good quality and a positive brand image will increase purchases and build customer loyalty. Keywords: Food Quality, Brand Image, Purchasing Decisions